(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Leadership philosophies play a significant role in determining the outcomes of information technology projects. Over the past few decades, there has been an evolution in the styles of leadership, moving from transactional leadership to transcendental leadership. The purpose of this research is to investigate whether or not there is a connection between the 3T leadership styles. In order to accomplish this goal, a convenience sample of one hundred people working in the information technology sector in Bangalore was selected. The review of the relevant literature served as the basis for the questionnaire, which was produced independently. The information that was gathered from the participants was analyzed with the help of a program called Statistical Package for the Social Sciences (SPSS) Version 25.0, which was made available by International Business Machines (IBM). In order to conduct a correlation study, the AMOS ® Software was utilized. The p value for the link between Transactional leadership and transformative and transcendent leadership is bigger than p=0.05, indicating that the relationship is statistically insignificant. There is a correlation, albeit a weak one, between transformational and transcendental styles of leadership in the field of information technology, and this association is statistically significant at a p-value of 0.000.